A timeline demarcating two waves of clonal deletion and Foxp3 upregulation during thymocyte development. Issue 4 (24th November 2015) - Hu, Daniel Y; Yap, Jin Y; Wirasinha, Rushika C; Howard, Debbie R; Goodnow, Christopher C; Daley, Stephen R
Abstract : Thymocytes that bind strongly to self‐antigens are prevented from becoming naive T cells by several mechanisms. They undergo clonal deletion at two stages of development; wave 1 in immature thymocytes lacking the medulla‐homing chemokine receptor, CCR7, or wave 2 in more mature CCR7 + thymocytes. Alternatively, self‐reactive thymocytes upregulate Foxp3 to become T‐regulatory cells. Here, we describe the differential timing of the two waves of deletion and Foxp3 upregulation relative to the immature proliferating stage. Proliferating thymocytes were pulse‐labeled in normal C57BL/6 mice with 5‐ethynyl‐2'‐deoxyuridine (EdU). Thymocytes progressed into wave 1 (CCR7 − ) and wave 2 (CCR7 + ) of clonal deletion ~2 and 5 days after proliferation, respectively. Foxp3 upregulation occurred between 4 and 8 days after proliferation, predominantly in thymocytes with a Helios + CCR7 + phenotype. These findings establish a timeline that suggests that wave 1 of clonal deletion occurs in the thymic cortex, whereas wave 2 and Foxp3 upregulation both occur in the thymic medulla.